2008
DOI: 10.1044/0161-1461(2008/07-0080)
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic Awareness Skill of Speech-Language Pathologists and Other Educators

Abstract: SLPs have relative expertise in phonemic awareness, yet their performance may not be proficient. Three recommendations are discussed: (a) Increase the phonemic awareness skill of all educators, (b) revise instructional materials to enhance educators' efforts to provide accurate and effective phonemic awareness instruction, and (c) include SLPs as members of the team responsible for phonemic awareness instruction and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 25 publications
5
70
0
2
Order By: Relevance
“…When the level of analysis of children's spellings is simply right or wrong, misspellings provide little guidance as to how to approach instruction. Additionally, several researchers in the US have reported that teachers possess insufficient knowledge of linguistic structure to provide highly effective literacy instruction (e.g., Carreker et al, 2010; Cunningham, Perry, Stanovich, & Stanovich, 2004; Moats, 1994; Spencer, Schuele, Guillot, & Lee, 2008), and less than 45% of pre-service teachers in Australia believe they are sufficiently prepared to teach spelling or phonics (Louden & Rohl, 2006). Such findings point to a lack of teacher preparedness to analyse misspellings beyond correct/incorrect with the purpose of guiding instructional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…When the level of analysis of children's spellings is simply right or wrong, misspellings provide little guidance as to how to approach instruction. Additionally, several researchers in the US have reported that teachers possess insufficient knowledge of linguistic structure to provide highly effective literacy instruction (e.g., Carreker et al, 2010; Cunningham, Perry, Stanovich, & Stanovich, 2004; Moats, 1994; Spencer, Schuele, Guillot, & Lee, 2008), and less than 45% of pre-service teachers in Australia believe they are sufficiently prepared to teach spelling or phonics (Louden & Rohl, 2006). Such findings point to a lack of teacher preparedness to analyse misspellings beyond correct/incorrect with the purpose of guiding instructional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For struggling learners, in need of and reliant on direct, explicit instruction (Moats, 1994;Moats & Lyon, 1996), inaccurate and contradictory instruction can create substantial obstacles for learning. A teacher's limited knowledge base may impede a child's educational progress (Spencer, Schuele, Guillot, & Lee, 2008). Therefore, teachers must know much about the structure of language and research-based reading and spelling instruction to teach reading effectively to a diverse student population (Moats, 2009).…”
Section: Signed: Rebecca a Cohenmentioning
confidence: 99%
“…This is in spite of the fact that SLPs are, arguably, among the professionals best equipped to perform and support development of these and other foundational language concepts and skills. A recent study by Spencer, Schuele, Guillot, and Lee (2008) found that, although not at mastery level, SLPs demonstrated superior knowledge of three levels of PA skills when compared with reading teachers, special education teachers, and kindergarten and grade 1 teachers. The practice of leaving SLPs out of the instructional loop effectively reduces the potential impact of interventions for struggling readers.…”
Section: Recent Efforts To Reform Reading Instructionmentioning
confidence: 94%